A step too far? Leader racism inhibits transgression credit. (22nd September 2014) - Abrams, Dominic; Travaglino, Giovanni A.; Randsley de Moura, Georgina; May, Philip J.
Abstract Prior research established that when in‐group leaders commit serious transgressions, such as breaking enforceable rules or engaging in bribery, people treat them leniently compared with similarly transgressive regular group members or out‐group leaders ('transgression credit'). The present studies test a boundary condition of this phenomenon, specifically the hypothesis that transgression credit will be lost if a leader's action implies racist motivation. In study 1, in a corporate scenario, a transgressive in‐group leader did or did not express racism. In study 2, in a sports scenario, an in‐group or out‐group leader or member transgressed rules with or without a racist connotation. Both studies showed that in‐group transgressive leaders lost their transgression credit if their transgression included a racial connotation. Wider implications for constraining leaders' transgressions are discussed. Copyright © 2014 John Wiley & Sons, Ltd.